2001
DOI: 10.1128/aac.45.12.3416-3421.2001
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 -Mediated Drug Resistance in Candida dubliniensis

Abstract: Candida dubliniensis is a recently described opportunistic fungal pathogen that is closely related to Candida albicans. Candida dubliniensis readily develops resistance to the azole antifungal agent fluconazole, both in vitro and in infected patients, and this resistance is usually associated with upregulation of the CdMDR1 gene, encoding a multidrug efflux pump of the major facilitator superfamily. To determine the role of CdMDR1 in drug resistance in C. dubliniensis, we constructed an mdr1 null mutant from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 21 publications
(19 reference statements)
1
70
0
2
Order By: Relevance
“…The mechanisms of resistance to azole drugs have been studied extensively (18,19,21,27,28,32,36,37,40,42,43). However, a large percentage (50%) of drug-resistant clinical isolates from a reported collection have unknown mechanisms of resistance (40).…”
mentioning
confidence: 99%
“…The mechanisms of resistance to azole drugs have been studied extensively (18,19,21,27,28,32,36,37,40,42,43). However, a large percentage (50%) of drug-resistant clinical isolates from a reported collection have unknown mechanisms of resistance (40).…”
mentioning
confidence: 99%
“…Molecular analysis of fluconazoleresistant C. dubliniensis isolates and in vitro-generated fluconazole-resistant derivatives has shown that in each case, the fluconazole resistance phenotype is associated with increased expression of the CdMDR1 gene encoding the multidrug transporter CdMdr1p (13). Wirsching et al demonstrated that targeted deletion of both copies of CdMDR1 in a C. dubliniensis clinical isolate with reduced susceptibility to fluconazole was sufficient to render the null mutant susceptible to fluconazole (35).…”
mentioning
confidence: 99%
“…This allowed amplification of the 5Ј and 3Ј ends of the CdCDR1 ORF and the entire plasmid vector (21). These primers contained SacII and XhoI restriction endonuclease recognition sequences that enabled the insertion of the SacII/XhoI fragment of pSFI1 (containing the site-specific recombinase FLP and the MPA resistance gene) (34,35), thereby replacing the central region of the CdCDR1 ORF to create plasmid pCDR⌬1. To create the second construct, the internal AccI/ BamHI fragment of CdCDR1 was cloned into pUC19 and subjected to inverse PCR with the primer pair 6F-6R (Table 2; Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of CdMDR1 has been shown to be involved in mediating a reduced accumulation of drug in fluconazole-resistant clinical isolates and in-vitro-generated derivatives [38]. Furthermore, the role of CdMDR1 in fluconazole resistance has been confirmed by the disruption of both alleles of the gene in a fluconazoleresistant clinical isolate overexpressing CdMDR1 [39].…”
Section: Mechanisms Of Azole Resistance In C Dubliniensismentioning
confidence: 84%